2020
DOI: 10.24815/jaroe.v3i3.17757
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Takaful Patronage Among Entrepreneurs in Sabon Gari Market, Kano State, Nigeria

Abstract: Objective – This paper examined the determinants of Takaful patronage among the entrepreneurs in Sabon Gari market of Kano metropolis, Nigeria. Design/methodology – The paper adopted survey research approach through the use of questionnaire. Respondents were selected using a purposive sampling technique. Multivariate regression was adopted to test the hypothesized model of the study using variance-based SEM. The data was analyzed using Smart-PLS 3. Results – The results show that religiosity, trust and confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…While some studies found 0.600 to be acceptable, others found multiple 0.600 to be unacceptable. The Cronbach alpha is acceptable since it's above 0.60 (Sulaiman et al, 2020). The measures in this research are dependable and accurate is a logical assumption to make.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…While some studies found 0.600 to be acceptable, others found multiple 0.600 to be unacceptable. The Cronbach alpha is acceptable since it's above 0.60 (Sulaiman et al, 2020). The measures in this research are dependable and accurate is a logical assumption to make.…”
Section: Resultsmentioning
confidence: 84%
“…Cronbach's alpha should be at least 0.70 (Sulaiman et al, 2020). While some studies found 0.600 to be acceptable, others found multiple 0.600 to be unacceptable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation